An integrated and dynamic framework for assessing sustainable resilience in complex adaptive systems - Nelson, Katherine S.; Gillespie-Marthaler, Leslie; Baroud, Hiba; Abkowitz, Mark; Kosson, David (My University, 2020)
Growing awareness of climate change and resulting impacts to communities have generated increasing interest in understanding relationships between vulnerability, resilience, sustainability, and adaptive capacity, and how these concepts can be combined to better assess the quality of complex adaptive systems over time. Previous work has described interactions between these concepts and the value-added should they be integrated and applied in a strategic manner, resulting in a new understanding of system quality defined as sustainable resilience. However, a framework for explicitly integrating vulnerability, resilience, and sustainability assessment to develop understanding of system sustainable resilience has yet to be proposed. This paper presents a high-level, integrated and dynamic framework for assessing sustainable resilience for complex adaptive systems. We provide a set of functional definitions, a description of each step in the proposed assessment process, and walk through an example application of the framework, including a discussion of preliminary analyses, technical methodologies employed, and suggested future advances.
Keywords: Sustainable resilience; Resilience; Vulnerability; Adaptive capacity; Sustainability; Complex adaptive systems